(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2019)
Abstract This article examines one of the Saheeh hadith about women as the majority of the inhabitants of Hell and its weakness from the side of reason and religion. The hadith is judged by feminists as a misogynistic hadith. In this paper, the author examines the hadith from its takhreej, then analyses the isnaad and matan and exposes the sharh of the scholars.In each discussion the author also sought to relate it to the contemporary context while giving a critical notes of the feminists ’ understanding of the hadith. Through this brief study, it can be concluded that what feminists accused that this hadith is misogynistic is not true. Their judgment is that the hadith is of questionable quality, unreasonable, and irrelevant to the context of the present because it discredits women, as well as improper assumptions. After the study carefully, it can be concluded that from the quality, this hadith should not be questioned again his validity because he narrated by Bukhari and Muslim and other scholars in al- Kutub al-Tis’ah. It is also from the side of matan. There is no representation of this hadith that women are imperfect or inferior beings. This understanding can be achieved, when the hadith is well understood, comprehensive, holistic and neither partial nor atomistic, nor seasoned with the spirit of humanism or Western feminism that is absolutely not essentially in Islam. Islam is a religion that is very upholding the degree and dignity of women. There is no verse found in the Qur’an or hadith which degrading or discredits women as accused by feminists.